Passive Aerial Righting and Safe Landing of a Small Bio-Inspired Jumping Robot - Kim, Baekgyeom; Ortega-Jimenez, Victor M.; Bhamla, M. Saad; Koh, Je Sung (2024 IEEE 7th International Conference on Soft Robotics, RoboSoft 2024, 2024)
Controlled landing is essential for biological and engineered jumpers to perform repetitive jumps and avoid damage to the body. In this paper, we introduce a bio-inspired jumping robot. This robot, small in scale (body length of approximately 20 mm) and lightweight (around 100 mg), can jump directionally and land with a controlled posture. Its torque reversal catapult-based jumping mechanism facilitates rapid takeoff at a speed of 3 m/s and achieves a maximum jumping height of approximately 22 times its size. This performance is remarkably similar to the height reached by springtails. The aerodynamic torque, induced by drag flaps, can reduce the body's angular velocity by 70% compared to that of an uncontrolled robot. Moreover, the robot's mid-air posture can be passively controlled through an enhanced stable equilibrium.
Keywords: Aerodynamic torque; Jumping mechanisms; Jumping robot; Performance; Safe landing; Stable equilibrium